QuarkXPress for dummies - Nelson, Jay J. (Hoboken, New Jersey : John Wiley & Sons, Inc., 2017)
"Inside ... Navigate the interface ; Build a layout ; Synch and collaborate ; Format text and paragraphs ; Work with tables ; Add pictures ; Prep files for print ; Output your work to digital"--Back cover.
Includes index.
"In full color"--Cover.
"Create designs for print or digital project ; Add eye-popping text and graphics ; Share projects across a team"--Cover.
"Learning made easy"--Cover.
Keywords: QuarkXPress (Computer file); QuarkXPress (Computer file); Desktop publishing; Desktop publishing